If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2.3 = c + -5.1 Reorder the terms: 2.3 = -5.1 + c Solving 2.3 = -5.1 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. 2.3 + -1c = -5.1 + c + -1c Combine like terms: c + -1c = 0 2.3 + -1c = -5.1 + 0 2.3 + -1c = -5.1 Add '-2.3' to each side of the equation. 2.3 + -2.3 + -1c = -5.1 + -2.3 Combine like terms: 2.3 + -2.3 = 0.0 0.0 + -1c = -5.1 + -2.3 -1c = -5.1 + -2.3 Combine like terms: -5.1 + -2.3 = -7.4 -1c = -7.4 Divide each side by '-1'. c = 7.4 Simplifying c = 7.4
| 21x-77=0 | | 5x+3y=65 | | 5s-25=2s+11 | | Cos(3x-30)=Sin(7x+50) | | 4-2cosx+5sinx=0 | | x-(-9)=7.9 | | 0.2xd+3=4 | | 4c+2p=45 | | 3x^2-13x+36=0 | | h=16t^2+40t+5 | | m^2+2m-575=0 | | 8x^4-20x^3-8x^2+20x=0 | | (a+3b)(2a-5b)= | | 9m+30=33 | | 6x(6x-5)-3(5-6x)= | | x^2+23-39=0 | | 16z^4-81z^4=0 | | a^2+6a+36=0 | | 6+ln(x+5)=8 | | Xsquared+5cubed=9cubed | | 9x^4-16=10x^2-17 | | 8x-18=36-6x | | 3*(15-x)=18 | | 2(3x-1)=4 | | 3*(x-15)=18 | | 5(7m-3)=14(2m+5) | | 3*(x-15)=48 | | V=6(8x+2)(5x-4)-10(5x-4) | | (2y-1)dy=(3x^2+1)dx | | 4x=190 | | (2y-1)dy=(3x+1)dx | | 2ln(5x+1)=14 |